The impact of the new organizational forms of the economy based on technological means in the world of work - Calderón Paredes, Cecilia (2019)
The Congress of the Republic of Peru has received two bills with the purpose of including legal  relationships composed of digital platforms, the companies involved and those who provide services for these platforms within the scope of Labor Law Regulations as a way to prevent them from being improperly excluded from such application of the law.This article explores the concept of on-demand economy and the economy’s new organizational methods that has been propelled by technological advances in the world of work and examines them through the review of international jurisprudence.